Evaluasi Mutu Cookies Garut yang Digunakan pada Program Pemberian Makanan Tambahan (PTM) untuk Ibu Hamil - Steisianasari Mileiva; Nurheni Sri Palupi; Feri Kusnandar (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2017)
During pregnancy, nutritional deficiencies often occur due to an increase in nutrition needs. As the deficiencies happens, the mother is at risk of giving birth to a baby with Low Birth Weight (LBW), neural tube defects, and disability. One way of prevention is to implement the Feeding program for pregnant women. In the Feeding program of South East Asian Food and Agricultual Science and Technology (SEAFAST) Center, arrowroot (garut) cookies are fortified with iron (Fe), zinc (Zn), iodine (I), vitamin A, vitamin C, and folic acid. Research carried out included evaluating functional characteristics (nutrient content), organoleptics, and shelf life of Non Fortified Cookies (CNF) and Fortified Cookies (CF). Some levels of nutrients do not fully meet the quality requirements of the Indonesian National Standard (SNI) for biscuits. Consumption ± 56 g of cookies per day is not enough for additional nutritional needs for pregnant women. Some deficiencies can be fulfilled and even exceeded by consuming milk, but lack of folic acid is still very large. The amount and type of fortification did not cause CF sensory deviations. Fortification of vitamins and minerals does not provide much difference between the shelf life of CNF and CF as determined by the critical moisture content approach.